Frequency of opportunistic infection in PL HIV and its role in monitoring of ART 1 failure - Singh, Narendra; Kumar, Lalit; Singh, Desh Nidhi; Kumar, Vipin (International Journal of Advances in Medicine, 2020)
Background: There is so many opportunistic infection is present in PL HIV patient when patient immunity disturbed and their CD4 count decreased .this study was conducted for frequency of opportunistic infection in PL HIV and its role in monitoring of ART 1 failure. Aims and objective was to study the frequency of opportunistic infection in PL HIV and its role in monitoring of ART1 failure. Methods: This study was conducted in ART plus centre K.P.S. Post Graduate Institute of Medicine (G.S.V.M. Medical College, Kanpur) tertiary care teaching hospital and is clinical (assessment with investigation) continuous longitudinal, prospective and retrospective, observational, single centre hospital based study at ART Centre, Kanpur and considered All the patient on 1st line ART treating attending in centre were screened for treatment failure decided by SACEP from 2016 to 2018. Results: In this study there was opportunistic infection present that maximum in oral candidiasis but overall tuberculosis is maximum that is considered pulmonary tuberculosis, extra pulmonary tuberculosis, tubercular lymphadenitis and tubercular pericarditis, Abdominal knocks, TBM. LRTI and chronic diarrhea is also present. The male and rural area are more having opportunistic infections and all are have CD4 count 100 to 200 micrometer /Litre. Conclusions: The opportunistic infection mostly are oral candidiasis and tuberculosis, present in CD4 count in the range of 100-200 /ml.it is the indication of ART failure during treatments.